Subacute Transplantation of Native and Genetically Engineered Neural Progenitors Seeded on Microsphere Scaffolds Promote Repair and Functional Recovery After Traumatic Brain Injury. (February 2019) - Skop, Nolan B.; Singh, Sweta; Antikainen, Henri; Saqcena, Chaitali; Calderon, Frances; Rothbard, Deborah E.; Cho, Cheul H.; Gandhi, Chirag D.; Levison, Steven W.; Dobrowolski, Radek
There is intense interest and effort toward regenerating the brain after severe injury. Stem cell transplantation after insult to the central nervous system has been regarded as the most promising approach for repair; however, engrafting cells alone might not be sufficient for effective regeneration. In this study, we have compared neural progenitors (NPs) from the fetal ventricular zone (VZ), the postnatal subventricular zone, and an immortalized radial glia (RG) cell line engineered to conditionally secrete the trophic factor insulin-like growth factor 1 (IGF-1). Upon differentiation in vitro, the VZ cells were able to generate a greater number of neurons than subventricular zone cells. Furthermore, differentiated VZ cells generated pyramidal neurons . In vitro, doxycycline-driven secretion of IGF-1 strongly promoted neuronal differentiation of cells with hippocampal, interneuron and cortical specificity. Accordingly, VZ and engineered RG-IGF-1-hemagglutinin (HA) cells were selected for subsequent in vivo experiments. To increase cell survival, we delivered the NPs attached to a multifunctional chitosan-based scaffold. The microspheres containing adherent NPs were injected subacutely into the lesion cavity of adult rat brains that had sustained controlled cortical impact injury. At 2 weeks posttransplantation, the exogenously introduced cells showed a reduction in stem cell or progenitor markers and acquired mature neuronal and glial markers. In beam walking tests assessing sensorimotor recovery, transplanted RG cells secreting IGF-1 contributed significantly to functional improvement while native VZ or RG cells did not promote significant recovery. Altogether, these results support the therapeutic potential of chitosan-based multifunctional microsphere scaffolds seeded with genetically modified NPs expressing IGF-1 to promote repair and functional recovery after traumatic brain injuries.